AUGMENTED REALITY: IMPROVEMENT OF CRITICAL THINKING BASED ON STUDENTS' INITIAL MATHEMATICAL ABILITY - Angraini, Lilis Marina; Alzaber; Debby Permata Sari; Ilham Muhammad (Indonesian Journal of Teaching and Learning, 2023)
This research is motivated by the importance of mathematical critical thinking skills for students, as well as the rapid development of information technology in the digital era. This study specifically aims to improve students' mathematical critical thinking skills through the application of Augmented Reality (AR)-based learning media with 3D unity that can be used in online learning and offline learning based on Initial Mathematical Ability (IMA). Augmented Reality is a technology that combines three-dimensional virtual objects into a real environment and then projects these virtual objects in real-time. While the initial mathematical ability is one of the factors that influence the learning of mathematics, the higher the initial mathematical ability of a student, the better the level of the student's mathematical critical thinking ability. This research is quantitative research (quasi-experimental), while the research subjects are students at one of Pekanbaru's state junior high schools class VII for the academic year 2022/2023, as many as 30 students who are randomly selected by the class. This research was conducted on the material of flat shapes, especially triangles and quadrilaterals. The data collection method used was a mathematical critical thinking ability test. The test result data was processed by statistical tests, including a normality test, homogeneity test and two-way ANOVA test. The results showed that the improvement of mathematical critical thinking skills of students who received learning using augmented reality media with Unity 3D was better than the improvement of mathematical critical thinking skills of students who received conventional learning based on students' initial mathematical abilities.